Facile Synthesis of Sulfur-Modified FeMnO₃-FeSO₃ as a High-Affinity Adsorbent for Efficient Antimony Removal - Tianning Wang; Linan Shao; Xiaosong Yang; Mengchang He (Water, Air, & Soil Pollution, 2026)

All in one: AIE-featured carbon dots with antibacterial activity for multivariate detection of Ag+, Hg2+ and BSA in real samples - Yu Gao; Linan Zhou; Qingqing Peng; Tingting Cui; Ziyi Guan; Fang Zhang; Li Wang; Huiyi Yang; Fang Chai (Journal of Environmental Chemical Engineering, 2026)

Orange-emissive nitrogen doped carbon dots as fluorescent for rapid sensing Ag+ in food water and soil - Dehong Xu; Siqi Chen; Linan Zhou; Fang Zhang; Huiyi Yang; Liangzi Cao; Rongxin Tan; Fang Chai (Journal of Environmental Chemical Engineering, 2026)

ABEEM/MM Magnesium Force Field for Proteins and Aqueous Solutions - Jing Zhang; Linan Lu; Runqiang Yu; Linlin Liu; Lei Wang; Cui Liu; Lidong Gong; Zhongzhi Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Inequality in distribution of atmospheric particulate matters and their health exposure risk in Beijing-Tianjin-Hebei, China - Linan Guo; Yuehan Wang; Yi Yang; Yurong Zheng; Li Zhou; Wenbin Sun (Atmospheric Pollution Research, 2026)

Protective role of nano-selenium on Gymnocypris przewalskii under saline–alkaline stress: a comprehensive analysis of transcriptomics and metabolomics - Yanxia Chen; Zhaonan Li; Ying Yang; Tianxiu Liang; Shuchen Huang; Jingjing Zhang; Wenjie Jin; Linan Wang; Qingchun Yan; Changzhong Li (Fish Physiology and Biochemistry, 2026)

Daily global transpiration estimation (2001–2018) by integrating satellite solar-induced fluorescence and spatially heterogeneous slope parameter in a conductance-photosynthesis model - Jiaxin Jin; Linan Dong; Guojing Gan; Xingwang Fan; Ying Wang; Qiuan Zhu; Russell Doughty; Yuanwei Qin; Guishan Yang (Agricultural and Forest Meteorology, 2026)

Study on hydraulic condition optimization of a new permeable modular constructed wetland - Fangxing Zhao; Xinwen Zhang; Jianchao Yang; Zhiheng Ye; Shuo Liu; Linan Zhou; Yixin Wang; Zhenghe Xu (Journal of Environmental Chemical Engineering, 2025)

Low intensity ultrasound enhances volatile fatty acid production of waste activated sludge: Insights into extracellular polymeric substances and sludge rheological properties - Linan Zhang; Shuai Tian; Shi Yang; Yichun Zhu; Zuwen Liu (Journal of Environmental Management, 2025)

Stacking paper sheets into multi-purpose quick response sensing code with built-in nitrocellulose-membrane-free lateral flow assay for detecting tetracycline in food samples - Rong Cao; Yafei Lou; Zhiyuan Yang; Linan Sun; Azadeh Nilghaz; Miaosi Li; Junfei Tian (Food Chemistry, 2025)

Apomixis in kelp genetic improvement: Practices, challenges, and prospects - Linan Zhang; Nianchao Xue; Xiaojie Li; Xiufeng Zhou; Guanpin Yang (Aquaculture, 2025)

Depositional characteristics in the Lower Congo Basin during the Cenomanian-Turonian stage: Insights from fine-grained sedimentary rocks - Bin Zhang; Hongtao Zhu; Xianghua Yang; Zhiwei Zeng; Zhongheng Sun; Linan Pang; Tingting Yao (Marine and Petroleum Geology, 2024)

The dominant influence of muddy bottom currents on organic-rich fine-grained sedimentary rocks: The lower Congo Basin, west Africa - Bin Zhang; Hongtao Zhu; Xianghua Yang; Zhiwei Zeng; Huang Xing; Linan Pang (Marine and Petroleum Geology, 2024)

The divergence of DHN-derived melanin pathways in Metarhizium robertsii - Linan Xie; Yang Liu; Yujie Zhang; Kang Chen; Qun Yue; Chen Wang; Baoqing Dun; Yuquan Xu; Liwen Zhang (World Journal of Microbiology and Biotechnology, 2024)

Completely blocking the feminization by replacing Limnodilus spp. with Artemia salina to feeding XY Zig-zag eel (Mastacembelus armatus) - Baoyue Lu; Xiaowen Xue; Zhide Yu; Linan Zhang; Jinlin Yang; Yuwei Feng; Yiman Chen; Chong Han; Xiaoli Yin; Hu Shu (Aquaculture, 2024)

Use of statins and risks of ovarian, uterine, and cervical diseases: a cohort study in the UK Biobank - Xue-Feng Jiao; Hailong Li; Linan Zeng; Huazhen Yang; Yao Hu; Yuanyuan Qu; Wenwen Chen; Yajing Sun; Wei Zhang; Xiaoxi Zeng; Lingli Zhang (European Journal of Clinical Pharmacology, 2024)
Purpose To examine the associations between use of statins and risks of various ovarian, uterine, and cervical diseases, including ovarian cancer, endometrial cancer, cervical cancer, ovarian cyst, polycystic ovarian syndrome, endometriosis, endometrial hyperplasia, endometrial polyp, and cervical polyp. Methods We conducted a cohort study among female participants in the UK Biobank. Information on the use of statins was collected through verbal interview. Outcome information was obtained by linking to national cancer registry data and hospital inpatient data. We used Cox proportional hazards regression to examine the associations. Results A total of 180,855 female participants (18,403 statin users and 162,452 non-users) were included. Use of statins was significantly associated with increased risks of cervical cancer (adjusted hazard ratio (HR), 1.55; 95% confidence interval (95% CI), 1.05–2.30) and polycystic ovarian syndrome (adjusted HR, 4.39; 95% CI, 1.68–11.49). However, we observed no significant association between use of statins and risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial hyperplasia, endometrial polyp, or cervical polyp. Conclusion Our findings suggest that use of statins is associated with increased risks of cervical cancer and polycystic ovarian syndrome, but is not associated with increased or decreased risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial polyp, or cervical polyp.

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

Evidence that co-existing cadmium and microplastics have an antagonistic effect on greenhouse gas emissions from paddy field soils - Linan Liu; Xinzuo Yang; Rob M. Ellam; Qiang Li; Di Feng; Zhaoliang Song; Jingchun Tang (Journal of Hazardous Materials, 2024)

SENP3 mediates the activation of the Wnt/β-catenin signaling pathway to accelerate the growth and metastasis of oesophagal squamous cell carcinoma in mice - Pengzeng Wang; Linan Yang; Yin Guo; Shuliang Qi; Jia Liang; Guo Tian; Ziqiang Tian (Functional & Integrative Genomics, 2024)

CNT-based water-induced generator for effective self-powered devices via superior synergism between electrokinetic and galvanic effects - Linan Xu; Wenxing Wang; Xiaoguang Li; Hongjian Yu; Xinyuan Liu; Yang Zhang; Hongyang Xu; Song Lin; Xing Yi Ling; Haitao Li (Chemical Engineering Journal, 2023)

Remote sensing assessment of the ecological benefits provided by national key ecological projects in China during 2000–2019 - Quanqin Shao; Shuchao Liu; Jia Ning; Guobo Liu; Fan Yang; Xiongyi Zhang; Linan Niu; Haibo Huang; Jiangwen Fan; Jiyuan Liu (Journal of Geographical Sciences, 2023)

Identification and Characterization of Long Non-Coding RNAs Involved in Sex-Related Gene Regulation in Kelp Saccharina japonica - Meihan Bai; Shutao Yue; Weiwei Wang; Xinxin Du; Xiaojie Li; Guanpin Yang; Linan Zhang (Journal of Ocean University of China, 2023)

The effects of metals and mixture exposure on lung function and the potential mediating effects of oxidative stress - Hao Zeng; Bohua Dong; Nan Wang; Wenzhe Xu; Linan Guo; Jiajia Liu; Bo Fang; Lei Zhang; Qian Wang; Wenqi Yang; Manman Wang (Environmental Geochemistry and Health, 2023)

Silicon (Si) modification of biochars from different Si-bearing precursors improves cadmium remediation - Linan Liu; Xinzuo Yang; Shakeel Ahmad; Xiaolong Li; Cholnam Ri; Jingchun Tang; Robert Mark Ellam; Zhaoliang Song (Chemical Engineering Journal, 2023)

Recognition and Prediction of Source Rocks of the Madingo Formation in the Lower Congo Basin - Youran Yang; Xianghua Yang; Wanzhong Shi; Hongtao Zhu; Wei Wang; Hongquan Kang; Linan Pang (Journal of Earth Science, 2023)

Exposure to barium and blood pressure in children and adolescents: results from the 2003–2018 National Health and Nutrition Examination Survey - Hao Zeng; Qiong Wang; Haotian Wang; Linan Guo; Bo Fang; Lei Zhang; Xuesheng Wang; Qian Wang; Wenqi Yang; Manman Wang (Environmental Science and Pollution Research, 2022)

Comparative genomic analysis of different virulence strains reveals reasons for the increased virulence of Aeromonas veronii - Bintong Yang; Chong Chen; Yufeng Sun; Linan Cao; Dongxing Zhang; Wuwen Sun; Lei Zhang; Guiqin Wang; Xiaofeng Shan; Yuanhuan Kang; Aidong Qian (Journal of Fish Diseases, 2021)
Aeromonas veronii is an important zoonotic and aquatic agent. More and more cases have shown that it has caused huge economic losses in the aquaculture industry in addition to threatening human health. But the reasons for the increasing virulence of A. veronii are still unclear. In order to further understand the reasons for the increased virulence of A. veronii , we conducted a comparative analysis of the genomes of A. veronii with different virulence. The analysis revealed that there are multiple virulence factors, such as those related to fimbriae, flagella, toxins, iron ion uptake systems and type II, type III and type VI secretion systems in the virulent strain TH0426 genome. And comparative analysis showed that there were two complete type III secretion systems (API1 and API2), of which the API2 and iron ion transport system were unique to the TH0426 strain. In addition, TH0426 strain also has unique functional gene clusters, which may play important roles in terms of resisting infection, adapting to different environments and genetic evolution. These particular virulence factors and gene clusters may be the important reasons for the increased virulence. These insights will provide a reference for the study of the pathogenesis of A. veronii .

Characterization of fossils and typomorphic minerals and its implications for source rocks in the Lower Congo Basin - Youran Yang; Xianghua Yang; Wanzhong Shi; Hongtao Zhu; Wei Wang; Hongquan Kang; Linan Pang (Arabian Journal of Geosciences, 2020)

Phosphorus removal from wastewater by waste concrete: influence of P concentration and temperature on the product - Xiao Liu; Huiyuan Zhong; Yong Yang; Linan Yuan; Shibo Liu (Environmental Science and Pollution Research, 2020)

Crude oil removal from aqueous solution using raw and carbonized Xanthoceras sorbifolia shells - Linan Liu; Lihua Wang; Wenhong Song; Liang Yang; Liming Yin; Shaopan Xia; Hailong Wang; Peter James Strong; Zhaoliang Song (Environmental Science and Pollution Research, 2018)

Ecological stoichiometry of nitrogen, phosphorous, and sulfur in China’s forests - Yuntao Wu; Hongyan Liu; Zhaoliang Song; Xiaomin Yang; Zichuan Li; Qian Hao; Linan Liu (Acta Geochimica, 2017)

Effects of topography and vegetation on distribution of rare earth elements in calcareous soils - Zhaoliang Song; Yuntao Wu; Xiaomin Yang; Zijuan Xu; Linan Liu; Xiaodong Zhang; Qian Hao; Shaobo Sun; Guilin Han; Congqiang Liu (Acta Geochimica, 2017)

Characterization of genome-wide microsatellites of Saccharina japonica based on a preliminary assembly of Illumina sequencing reads - Linan Zhang; Jie Peng; Xiaojie Li; Cuiju Cui; Juan Sun; Guanpin Yang (Journal of Ocean University of China, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Relationship between the velvet-like texture of flower petals and light reflection from epidermal cell surfaces - Yang Zhang; Tianxun Sun; Linan Xie; Takahiro Hayashi; Saneyuki Kawabata; Yuhua Li (Journal of Plant Research, 2015)

Effect of temperature on the development of Saccharina japonica gametophytes - Linan Zhang; Cuiju Cui; Xiaojie Li; Zhuangzhi Zhang; Shiju Luo; Guangjin Liang; Yanling Liu; Guanpin Yang (Journal of Applied Phycology, 2013)

Determination of ochratoxin A in traditional Chinese medicinal plants by HPLC–FLD - Lei Yang; Linan Wang; Jianyu Pan; Lan Xiang; Meihua Yang; Antonio F. Logrieco (Food Additives & Contaminants: Part A, 2010)

Biodegradation of avermectin by Bacteroidetes endosymbiont strain LYH - Zaixing Li; Cunyi Song; Jingliang Yang; Jianbo Guo; Linan Xing (World Journal of Microbiology and Biotechnology, 2008)